Object control skills of children and youth with Autism Spectrum Disorder - Valley, Megan (My University, 2013)
Autism spectrum disorder (ASD) is the fastest growing classification of disability in the U.S., with 1 in every 50 births resulting in a person diagnosed with ASD (Centers for Disease Control and Prevention, 2013). Several studies have identified a delay in the gross motor skills of children with ASD (Breslin & Rudisill, 2011). This is a significant concern for the field of adapted physical education since there will be more students with ASD who may be in need of specially designed physical education services. Understanding these delays is important for those who provide services to students with ASD. The purpose of this study was to compare the object control skill functioning of children and youth with ASD to their typically developing peers. Participants were (N = 27) 4-18 year olds with ASD who were tested on the object control skill subtest in the Test of Gross Motor Development-2 (Ulrich, 2000). Results indicated that those with ASD are delayed an average of 57 months behind their typically developing peers. Descriptive analysis suggests that the greatest delay occurs in participants with autistic disorder, delay increases with age, and dribbling and rolling skills were the most delayed compared to other object control skills.
Keywords: Autistic children; Autism--Exercise therapy.; Children with autism spectrum disorders.